Relations Between He I λ10830 Absorption Strength and Stellar Activity Amongst Dwarf Stars. (10th November 2016) - Smith, Graeme H.
Abstract: Correlations are identified between the strength of the λ10830 HeI triplet line and the following tracers of stellar activity amongst FGK dwarfs with colours of ( B − V ) > 0.47: coronal soft X-ray emission, emission in the λ1549 CIV and λ1335 CII lines originating from the transition region, and CaII H and K emission from the chromosphere. No such correlations are present amongst dwarfs with spectral type earlier than F6. In addition, G and K dwarfs with strong triplet lines show evidence of excess flux in the GALEX FUV band compared to weak-triplet-line dwarfs. The X-ray spectra of late-F, G, and K dwarfs with HeI triplets stronger than 160 mÅ have greater values of the ROSAT hardness ratio HR1 than are typical of weak-triplet dwarfs in the same range of spectral type. In other words, dwarfs later than F7V with strong HeI triplet lines tend towards harder 0.1–2.0 keV X-ray spectra than weak-triplet dwarfs, although values of HR1 −0.2 to +0.1 can still be encountered amongst a minority of weak-He-triplet stars. As regards, FGK main sequence stars the observational data on the λ10830 triplet line remains sparse. Progress could be made through spectroscopy of high resolution for samples of hundreds of stars, selected on the basis of having other measures of chromospheric and coronal activity available.